Obtaining superhard composites of the BL group in the cBN(Al)-SiB4-WC system under high pressure and high temperature conditions - Stratiichuk, D.A.; Turkevich, V.Z.; Bushlya, V.M.; Ståhl, J.-E.; Bilyavyna, N.M. (Reports of the National Academy of Sciences of Ukraine, 2019)
The processes of formation of ceramicmatrix materials in the cBN(Al)-SiB4 WC system under high pressure conditions (7.7 GPa) in the temperature range of 1600-2300 °C are studied. It is shown that, for the composition chosen by us (BL group), 60 % vol. cBN, 5 % vol. Al, 25 % vol. SiB4 and 10 % vol. WC, nonporous superhard materials are virtually formed in the entire temperature range with hardness of no less than 33 GPa and Young’s modulus of 613 GPa, which is attributable to the formation of a highstrength ceramic matrix both as a result of the liquidphase sintering using aluminium and of an active chemical interaction of silicon tetraboride with WC. It is demonstrated by experiments that the micropowder consolidation process should be carried out at temperatures of no less than 1800 °C. The heating of the system above 2200 °C leads to the excessive cBN graphitization and accumulative recrystallization in general. According to the XRD analysis, it was established that, as a result of the thermal decomposition of silicon tetraboride and further chemical reaction with WC, new compounds are formed: W2B5 and WSi2, and the original aluminum is oxidized to α-Al2O3, thereby relieving the system of excess oxygen. All new compounds formed in the course of producing the ceramics are represented by microcrystalline forms, not exceeding 1—3 μm in size, that are arranged in the intergranular space of the core matrix, which contributes to an additional increase in hardness and fracture resistance. The obtained superhard ceramic plates can be used for turning tempered (up to 60 HRC) and highalloyed (including inconel) steel at rising temperatures in the cutting area.